City and spectacle : a vision of pre-earthquake Lisbon - Câmara, Maria Alexandra Gago da (2014)
On the eve of the great earthquake of 1st November 1755, Lisbon was one of the most populated cities in Europe, a major sea port, international trading station and the political heart of an empire that extended from India to Brazil. Portrayed by some travellers and foreign residents as a mixture of abject misery, extreme religious devotion and baroque opulence and extravagance, the old Lisbon became a mythical city for 18th century Europeans whil e for the Portuguese it has remained so until today. After the catastrophe, Sebastião José de Carvalho e Melo (b. 1699–d.1782), the minister to King D. José (1750 –1777, b. 1714) and future Marquis of Pombal, with the vital assistance of Portuguese military engineers, built a city with a regular layout arranged in uniform blocks. The old Lisbon with its particular morphological and social characteristics disappeared. The aim of this project is to use Second Life® technology to recreate the Lisbon destroyed by the 1755 earthquake and on which the Lisbon planned by the military engineers Eugénio dos Santos and Carlos Mardel was built. It therefore consists of collaboration between two scientific approaches – historic and virtual language —thereby allowing the visualization of a memory. Using written documentation and iconography found in archives and national museums, we propose to reconstitute the city, including not only the urban design but also the architectonic fabric of the whole and the interiors of the most noteworth y buildings, such as the Royal Palace in Terreiro do Paço (Palace Courtyard), the Patriarchal See, the Opera House, the Corp us Christi Convent and the All Saints Hospital. This re-creation will include an audio component that provides the background noise of city-dwellers, as well as performances of the opera and other noteworthy events of Lisbon of the time. It will be complemented by small texts giving the historical context. It thus strives to recreate the spatial, architectural, social and cultural dimensions of Lisbon in the early 18th century.